The Challenges in Using eHealth Decision Resources for Surrogate Decision-Making in the Intensive Care Unit - Wan-Na Sun; Chi-Yin Kao (JMIR Publications, 2024)
The mortality rate in intensive care units (ICUs) is notably high, with patients often relying on surrogates for critical medical decisions due to their compromised state. This paper provides a comprehensive overview of eHealth. The challenges of applying eHealth tools, including economic disparities and information inaccuracies are addressed. This study then introduces eHealth literacy and the assessment tools to evaluate users' capability and literacy levels in using eHealth resources. A clinical scenario involving surrogate decision-making is presented. This simulated case involves a patient with a hemorrhagic stroke who has lost consciousness and requires medical procedures such as tracheostomy. However, due to the medical surrogate's lack of familiarity with eHealth devices and limited literacy in using eHealth resources, difficulties arise in assisting the patient in making medical decisions. This scenario highlights challenges related to eHealth literacy and solution strategies are proposed. In conclusion, effective ICU decision-making with eHealth tools requires a careful balance between efficiency with inclusivity. Tailoring communication strategies and providing diverse materials are essential for effective eHealth decision resources in the ICU setting. Health professionals should adopt a patient-centered approach to enhance the decision-making experience, particularly for individuals with limited eHealth literacy.